Military Technology, Character of War and Strategic Conceptions (Czech Journal of International Relations, 1966)
I heard someone say in a random discussion that the term contemporary military a foreign political concept automatically evokes in him the idea of ​​a whole galaxy the names of well-known bourgeois theoreticians, but he does not remember the name of any Marxist thinker in this context. H. Kissinger, H. Kahn, R. Aron, W. Rostow, L. Hart, P. Gallois and others have no equal in this field in the socialist countries. The register of Marxist workers remains relatively thin and short. The main reason for this fact is well known and very simple. The science of political strategy stagnated for a long time in our country for various reasons. In capitalist states, within the framework of existing possibilities and conditions, it developed strongly, especially in terms of intensity and quantity. (We see that in France alone, almost 1,000 titles have been published in recent years on topics related to issues of war and peace and military policy.)